MAQĀṢID AL-SYARĪ'AH DALAM KONSEP PEMILIHAN PASANGAN: STUDI KRITIS BAB NIKAH KITAB FATH AL-MU'IN - Hanifah Khairiyah Siregar; Amar Adly; Heri Firmansyah (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2026)
This study aims to analyze the concept of spouse selection in the marriage chapter of Fath al-Mu'in through the lens of maqāṣid al-syarī'ah, examining the extent to which its criteria compatibility (kafā'ah), religiosity (dīn), lineage (nasab), and physical attractiveness align with the higher objectives of Islamic law in preserving lineage (ḥifẕ al-nasl), preserving reason (ḥifẕ al-‘aql), and realizing family welfare (maṣlaḥah al-usrah). This research employs a qualitative method through library research and content analysis of the primary text of Fath al-Mu'in, compared against classical and contemporary maqāṣid al-syarī'ah frameworks, cross-madhhab juristic opinions, and Indonesian family-law regulations. The findings indicate that the spouse-selection criteria in Fath al-Mu'in are generally consistent with maqāṣid al-syarī'ah in the dimensions of ḥifẕ al-nasl and ḥifẕ al-dīn, although certain aspects particularly the emphasis on nasab-based kafā'ah and social status require contextual reinterpretation to avoid reinforcing social inequality in contemporary marriage practice.